Modification of Taxifolin Properties by Spray Drying - Amir Taldaev; Roman P. Terekhov; Irina A. Selivanova; Denis I. Pankov; Maria N. Anurova; Irina Yu. Markovina; Zhaoqing Cong; Siqi Ma; Zhengqi Dong; Feifei Yang; Yonghong Liao (MDPI AG, 2022)
Taxifolin is known as an active pharmaceutical ingredient (API) and food supplement due to its high antioxidant activity, multiple pharmacological effects, and good safety profile. Previously, taxifolin spheres (TS) were obtained from industrially produced API taxifolin in Russia (RT). In our work, we perform a pharmaceutical analysis of this new taxifolin material versus RT. TS is an amorphous material; however, it is stable without the polymer carrier, as confirmed by Fourier transform infrared spectroscopy. Both RT and TS demonstrate high safety profiles and are assigned to Class 1 of the Biopharmaceutical Classification System based on the results of experiments with MDCK cells. The water solubility of the new taxifolin form was 2.225 times higher compared with RT. Hausner ratios for RT and TS were 1.421 and 1.219, respectively, while Carr indices were 29.63% and 19.00%, respectively. Additionally, TS demonstrated sustained release from tablets compared with RT: the half-life values of tablets were 14.56 min and 20.63 min for RT and TS, respectively. Thus, TS may be a promising object for developing oral antiseptics in the form of orally dispersed tablets with sustained release patterns because of its anti-inflammatory, -protozoal, and -viral activities.